Developing Environmental Teaching Materials Based on Local Context and Environmental Literacy - Mukhyati, Mukhyati; Sriyati, Siti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This research was aimed to develop environmental teaching materials for senior high school based on local contexts of Bangka Island and environmental literacy. Research and Development designed by Borg & Gall was used with the following steps: research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, & main field testing. The limited testing was conducted at one school by involving 30 students from year ten and testing of wide scale was conducted at three schools involving 92 students. The teaching materials was developed follow the guidelines of developing environmental materials according to NAAEE. The six key characteristics of environmental materials which is environmental literacy oriented are: fairness & accuracy, depth, emphasis on skill building, action orientation, instructional soundness and usability. Data collection was conducted through observation, documentation, questionnaires, and test. Test validation by materials experts, technology experts, users, and readability test were conducted to ensure the quality of teaching materials. Feasibility of content and graphical aspects was measured through questionnaire, whereas the readability test was conducted by using cloze test. Data were analyzed qualitatively. The result showed: 1) the quality of teaching materials based on material experts validation was good categorized with a percentage of 76.3%, the technology experts validation was good categorized with a percentage of 75%, and the teacher validation, as a user, was excellent categorized with a percentage of 93.4%, 2) by using cloze test analysis, the teaching materials had a high readability. The product had been revised based on advice and corrections from validator, the result of limited testing, and testing of wide scale. The conclusions of this research is the development of teaching material based on local contexts of Bangka Island and environmental literacy can be implemented in learning process of environmental change concept.Keywords: local contexts, environmental teaching materials, environmental literacy